2015
DOI: 10.1111/acer.12624
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mechanisms Influencing the Relationship Between Alcohol Consumption and Peer Alcohol Use

Abstract: Background Alcohol consumption is typically correlated with the alcohol use behaviors of one’s peers. Previous research has suggested that this positive relationship could be due to social selection, social influence, or a combination of both processes. However, few studies have considered the role of shared genetic and environmental influences in conjunction with causal processes. Methods The current study uses data from a sample of male twins (N=1790) who provided retrospective reports of their own alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 41 publications
3
29
0
1
Order By: Relevance
“…The better model fit indices for factor, rather than item correlations indicated that friend drinking as a measured outcome may contribute to a substantial part of the general variance attributed to either common or unique environment for drinking. The association between genetic variance and friend use is also supported by previous literature documenting gene-environment correlations or interactions (Edwards et al, 2015; Harden et al, 2008). However, these associations stopped after late adolescence.…”
Section: Discussionsupporting
confidence: 72%
“…The better model fit indices for factor, rather than item correlations indicated that friend drinking as a measured outcome may contribute to a substantial part of the general variance attributed to either common or unique environment for drinking. The association between genetic variance and friend use is also supported by previous literature documenting gene-environment correlations or interactions (Edwards et al, 2015; Harden et al, 2008). However, these associations stopped after late adolescence.…”
Section: Discussionsupporting
confidence: 72%
“…Work in humans suggests that genetic contributions to alcohol abuse may be considerably stronger during adulthood compared to adolescence (van Beek et al ., 2012, Edwards et al ., 2015; also see Chorlian et al ., 2013; Guo et al ., 2015). Indeed, adolescent B6 mice voluntarily drink more ethanol than adults, an ontogenetic difference not observed in mice from the DBA/2J strain (Moore et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…That study also found that approximately 50-78% of the genetic variance in peer group deviance was attributable to genetic factors related to cannabis use [27][28][29]. Another study [30] reported that the heritability of perceived peer alcohol use ranged from 7% at age 12-14 to 38% by age 18, and that the relationship between peer alcohol use and one's own alcohol use was attributable to genetic factors with a correlation of 0.83. Taken together, these observations raise the possibility that polygenic risk for cannabis use may interface with peer cannabis use in several possible ways, ranging from a main effect to a potential interactive effect.…”
Section: Introductionmentioning
confidence: 84%
“…While peer use is readily viewed as an 'environmental' agent of risk, it can also represent heritable aspects of underlying behavior, with at least one study suggesting a heritability of 25-28% for general peer group deviance, a broad measure including peer marijuana use [26]. Another study [30] reported that the heritability of perceived peer alcohol use ranged from 7% at age 12-14 to 38% by age 18, and that the relationship between peer alcohol use and one's own alcohol use was attributable to genetic factors with a correlation of 0.83. Another study [30] reported that the heritability of perceived peer alcohol use ranged from 7% at age 12-14 to 38% by age 18, and that the relationship between peer alcohol use and one's own alcohol use was attributable to genetic factors with a correlation of 0.83.…”
Section: Introductionmentioning
confidence: 99%